2019
DOI: 10.1200/jco.2019.37.15_suppl.2034
|View full text |Cite
|
Sign up to set email alerts
|

GLIAVAX: A stratified phase II clinical trial of avelumab and axitinib in patients with recurrent glioblastoma.

Abstract: 2034 Background: Patients (pts) with recurrent glioblastoma (rGB) have a poor prognosis, and no treatment option demonstrated to improve survival in a randomized trial. Axitinib (AXI), an oral VEGFR 1-3 inhibitor has demonstrated single agent activity in rGB and reduces the need for corticosteroids (CS). Avelumab (AVE) is a fully human anti-PD-L1 IgG1 antibody with clinical activity in various tumor types. Combination of AXI and AVE may improve the outcome of pts with rGB. Methods: This open-label, dual-strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…GLIAVAX, a phase II trial of 54 patients with recurrent GBM treated with avelumab and axitinib demonstrated favorable tolerability but did not meet the primary endpoint goal with a 6-month progression-free survival (PFS-6) of only 18%. 79 The addition of pembrolizumab to bevacizumab, a VEGF inhibitor, also did not improve PFS-6. 80 Other TKI combinations being studied with PD-1 blockade include TTAC-001 (VEGFR-2/KDR) and lenvatinib (VEGFR1/2/3).…”
Section: Ctla-4mentioning
confidence: 99%
“…GLIAVAX, a phase II trial of 54 patients with recurrent GBM treated with avelumab and axitinib demonstrated favorable tolerability but did not meet the primary endpoint goal with a 6-month progression-free survival (PFS-6) of only 18%. 79 The addition of pembrolizumab to bevacizumab, a VEGF inhibitor, also did not improve PFS-6. 80 Other TKI combinations being studied with PD-1 blockade include TTAC-001 (VEGFR-2/KDR) and lenvatinib (VEGFR1/2/3).…”
Section: Ctla-4mentioning
confidence: 99%
“…Anderson Cancer Center, 2021). However, avelumab has not seen a similar level of success in GBM, having failed to meet the threshold for justifying further investigation in the GLIAVAX trial testing axitinib and avelumab combination use in rGBM patients following SOC (Neyns et al, 2019). Durvalumab has been FDA approved for bladder cancer and non-small cell lung cancer (NSCLC) and is currently being tested in a phase II trial for newly diagnosed unmethylated GBM patients (Ludwig Institute for Cancer Research, 2021).…”
Section: Anti-pd1/pdl1mentioning
confidence: 99%
“…Besides PD-1, preliminary results are available from the first two single-arm phase II studies which tested PD-L1 inhibitors in glioblastoma patients using efficacy as primary endpoints. In the first study conducted in recurrent glioblastoma, the combination of anti-PD-L1 antibody avelumab and axitinib (a tyrosine kinase inhibitor selective for VEGF receptors) did not meet the study threshold for activity (six-mo PFS being 18%) [19]. In the second study, the addition of PD-L1 inhibitor durvalumab to SOC resulted in a modest increase of OS for patients with newly diagnosed MGMT-unmethylated glioblastoma (durvalumab 15.1 mo vs. historical controls 12.7 mo) [20].…”
Section: Pd-l1 Inhibitor Trialsmentioning
confidence: 99%